Polydopamine Chelate Modified Separators for Lithium Metal Batteries with High‐Rate Capability and Ultra‐Long Cycling Life - Shixiang Liu; Qiang Liu; Pu Cheng; Xingkai Jia; Yinzhu Jiang; Xuan Zhang (Advanced Science)
Abstract Lithium metal batteries (LMBs) have gained significant attention because of their high theoretical energy density. However, under high‐rate charge and discharge conditions, lithium metal anodes are susceptible to dendrite formation, compromising battery safety. Creating multifunctional separators offers an effective and cost‐efficient solution for addressing fast charging and safety challenges in LMBs. This study proposes a method to prepare a functional separator by in situ growing a polydopamine copper chelate (PDA(Cu)) coating on a polypropylene (PP)/polyethylene (PE)/PP separator (PP/PE/PP@PDA(Cu)). The PDA(Cu) exhibits excellent electrolyte wetting properties and ion exclusion effects, contributing to high ionic conductivity (5.02 × 10−⁴ S cm−1) and high lithium‐ion (Li+) transference number (0.776). Owing to its strong adhesion to the lithium metal anode, the coating significantly suppresses the formation of lithium dendrites. The Li||Li symmetric cell with a PP/PE/PP@PDA(Cu) separator demonstrates highly stable lithium plating‐stripping cycles, lasting over 900 h. Additionally, the PDA(Cu) promotes the formation of a stable cathode electrolyte interphase (CEI) film on the LiFePO4 cathode surface. The LiFePO4||Li cell with a PP/PE/PP@PDA(Cu) separator maintains 85.1% of its capacity after 6000 cycles at 10 C. This work paves a novel path for designing separators to enhance the fast‐charging performance of LMBs and solve the challenges of lithium dendrite formation and long cycling life.